What the chicken knows : a new appreciation of the world's most familiar bird - Montgomery, Sy (Atria Books, 2024)
"For more than two decades, Sy Montgomery ... has kept a flock of chickens in her backyard. Each chicken has an individual personality (outgoing or shy, loud or quiet, reckless or cautious) and connects with Sy in her own way. In this short ... book, Sy takes us inside the flock and reveals all the things that make chickens such remarkable creatures: only hours after leaving the egg, they are able to walk, run, and peck; relationships are important to them and the average chicken can recognize more than one hundred other chickens; they remember the past and anticipate the future; and they communicate specific information through at least twenty-four distinct calls"--